Customer perception on the adoption of self-service technologies in Klang Valley/ Azlinda Hakim Lokman Hakim, Hairunnisa Mohamad Ibrahim and Pauline Tang Pei Lin - Lokman Hakim, Azlinda Hakim; Mohamad Ibrahim, Hairunnisa; Tang, Pauline Pei Lin (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
As self-service options have become more widespread, customers' interactions with service workers and technology have changed. Self-service technologies are increasingly valued by customers for their convenience, consistency, and control. Despite their increasing popularity, Malaysian hotels have yet to fully integrate self-service technologies into their daily operations. Self-service technologies (SSTs) help hotels to improve service standards, and the wide range of technological applications available allows hotels to choose the application that best matches the needs of their guests as well as the hotel's needs. Despite of numerous studies have been conducted in the scope of SST; the focus revolves around hotels in Klang Valley remained under-studied. The purpose of this study is therefore to 1) investigate customer perceptions of hotel self-service technology (SSTs). 2) to identify the elements that influence how selfservice technologies (SSTs) are perceived and used in hotels. Perceived usefulness has a positive link with intention to utilize SSTs, according to the findings. A self-administered questionnaires that focused on variables of ease of use, privacy, autonomy and effectiveness will be part of purposive sampling approach employed to furnish the relevance towards this study.